Trust in management in organizations - Kieron J. Meagher; Andrew Wait (IZA World of Labor, 2023)
It is not possible for a formal employment contract to detail everything an employee should do and when. Informal relationships, in particular trust, allow managers to arrange a business in a more productive way; high-trust firms are both more profitable and faster growing. For example, if they are trusted, managers can delegate decisions to employees with confidence that employees will believe the promised rewards. This is important because employees are often better informed than their bosses. Consequently, firms that rely solely on formal contracts will miss profitable opportunities.
Keywords: J24; J5; M12; M54; 330; management; trust; productivity; profitability